The influence of a visuospatial grounding task on intrusive images of a traumatic film. - Stuart, A; Holmes, E; Brewin, C (2006)
Nonclinical participants watched a trauma film under two processing conditions. During part of the film participants carried out a concurrent visuospatial grounding task consisting of the construction of shapes out of plasticine (modelling clay), while the rest of the film constituted a control, no task condition. The visuospatial task was predicted to selectively compete for processing resources required for intrusive image formation. As predicted, spontaneous intrusive images during the succeeding week were significantly less common from those parts of the film that coincided with the concurrent task. The task had no effect on levels of distress or peritraumatic dissociation, consistent with the hypothesis that intrusions were reduced because the task competed for resources necessary for encoding into an image-based memory system.